Resveratrol alleviates testicular toxicity induced by anti-PD-1 through regulating the NRF2-SLC7A11-GPX4 pathway - Tuerxun, Halahati·; Zhao, Yixin; Li, Yawen; Liu, Xingyu; Wen, Shuhui; Zhao, Yuguang (Frontiers in Immunology, 2025)
BackgroundFertility preservation is a critical concern for reproductive-age cancer survivors, as conventional cytotoxic therapies can cause irreversible damage to the reproductive system, potentially depriving them of the ability to have children in the future. Immune checkpoint inhibitors (ICIs), including anti-programmed cell death protein 1 (anti-PD-1), have become a standard therapeutic approach for various malignancies. However, the impact of ICIs on reproductive function and fertility is not well understood and remains a largely unexplored domain. Resveratrol (RSV), a plant-derived compound, has shown potential as an nuclear factor erythroid 2-related factor 2 (NRF2) agonist to counteract reproductive toxicity induced by various diseases, drugs, and environmental toxins.MethodsMale C57BL6/J mice with B16 melanoma were assigned into four groups. RSV and ICI/RSV groups received RSV (40 mg/kg) orally every other day for one month, while controls received the vehicle. ICI and ICI/RSV groups were injected with anti-PD-1 antibody (10 mg/kg) weekly, and controls received IgG2b kappa antibody. Parameters like body and testicular weight, sperm concentration, and western blot for ferroptosis markers were measured. Furthermore, oxidative stress biomarkers, lipid oxidation factors, and gonadal hormone levels were quantified using commercial kits.ResultsAnti-PD-1 therapy caused male reproductive dysfunction, as evidenced by reduced sperm concentration, altered gonadal hormone levels, and disruption of blood-testis barrier (BTB) integrity. Furthermore, ferroptosis was a key mechanism in anti-PD-1-induced testicular dysfunction, characterized by disrupted iron homeostasis, elevated lipid peroxidation, and suppression of the system Xc−/glutathione peroxidase 4 (GPX4) axis. Additionally, anti-PD-1 therapy diminished antioxidant defenses by inhibiting the NRF2 pathway, thereby increasing the susceptibility to ferroptosis. Crucially, RSV treatment ameliorated anti-PD-1-induced reproductive dysfunction. This was achieved by reducing T cell infiltration, lowering interferon-gamma levels, activating the NRF2 pathway, and maintaining iron and lipid homeostasis.ConclusionsOur study demonstrates that anti-PD-1 triggers oxidative stress and ferroptosis in the testis, causing male reproductive dysfunction. RSV may offer protection against testicular toxicity associated with anti-PD-1, particularly through its antioxidant and anti-ferroptosis properties.